Correlations between environmental conditions and Vibrio parahaemolyticus or Vibrio vulnificus in Pacific oysters from New Zealand coastal waters. Issue 3 (3rd July 2021) - King, Nicola J.; Pirikahu, Sarah; Fletcher, Graham C.; Pattis, Isabelle; Roughan, Brian; Perchec Merien, Anne-Marie
ABSTRACT: Vibrio parahaemolyticus and Vibrio vulnificus can be found in oysters in coastal environments. Vibrio vulnificus can induce life-threatening illness when ingested with oysters, while V. parahaemolyticus usually causes self-limiting gastroenteritis. This study investigated correlations between concentrations of these Vibrio species in Pacific oysters from eight New Zealand coastal regions (2008–2017), and seawater surface temperature (SST), salinity and rainfall. In the pooled data, most (88%) of the oyster samples were collected during summer and autumn. The prevalence of V. parahaemolyticus and V. vulnificus was 85% and 15%, respectively. Vibrio vulnificus was always detected in the presence of V. parahaemolyticus . Across all regions, V. parahaemolyticus concentration positively correlated with SST ( rS  = 0.60), but not with salinity ( rS  = −0.01). Vibrio vulnificus concentration weakly correlated with SST ( rS  = 0.26) and salinity ( rS  = −0.21). Linear and generalised additive models were investigated but none were satisfactory for prediction. Salinity and SST explained < 50% of the variability in V. parahaemolyticus concentrations, indicating that other environmental or biological factors contributed. When SST, salinity and rainfall 15 days prior to harvesting were investigated for one region, SST was the best pre-harvest indicator for elevated concentrations of both Vibrio species.